Pengaruh Green Accounting Terhadap Mfca Dalam Meningkatkan Keberlangsungan Usaha Serta Resource Efficiency Sebagai Variabel Moderating (Studi Kasus Pada Perusahaan Peraih Penghargaan Industri Hijau) - Windasari Rachmawati; Abdul Karim (Tirtayasa Ekonomika, 2021)
The use of the term green accounting has recently become popular with the increasing number of researches that raise green accounting in Indonesia. Green accounting deals with environmental information and environmental auditing systems and has been defined as' the identification, tracking, analysis, and reporting and cost information related to environmental aspects of an organization. The main role of green accounting is to address social environmental problems, as well as to have an impact on the achievement of sustainable development and the environment in any country, which affects corporate behavior in dealing with issues of social and environmental responsibility. MFCA is a key tool in a management approach known as flow management which aims specifically at managing manufacturing processes related to the flow of materials, energy and data.This study uses a statistical test tool with a moderation test, which shows that material flow cost accounting is measured from the cost of production, the area of production and the yield or value of production on business continuity, and green accounting has no effect on business continuity.